Identification of favorable SNP alleles and candidate genes for traits related to early maturity via GWAS in upland cotton. (December 2016) - Su, Junji; Pang, Chaoyou; Wei, Hengling; Li, Libei; Liang, Bing; Wang, Caixiang; Song, Meizhen; Wang, Hantao; Zhao, Shuqi; Jia, Xiaoyun; Mao, Guangzhi; Huang, Long; et al.
Abstract Background Early maturity is one of the most important and complex agronomic traits in upland cotton (Gossypium hirsutum L). To dissect the genetic architecture of this agronomically important trait, a population consisting of 355 upland cotton germplasm accessions was genotyped using the specific-locus amplified fragment sequencing (SLAF-seq) approach, of which a subset of 185 lines representative of the diversity among the accessions was phenotypically characterized for six early maturity traits in four environments. A genome-wide association study (GWAS) was conducted using the generalized linear model (GLM) and mixed linear model (MLM). Results A total of 81, 675 SNPs in 355 upland cotton accessions were discovered using SLAF-seq and were subsequently used in GWAS. Thirteen significant associations between eight SNP loci and five early maturity traits were successfully identified using the GLM and MLM; two of the 13 associations were common between the models. By computing phenotypic effect values for the associations detected at each locus, 11 highly favorable SNP alleles were identified for five early maturity traits. Moreover, dosage pyramiding effects of the highly favorable SNP alleles and significant linear correlations between the numbers of highly favorable alleles and the phenotypic values of the target traits were identified. Most importantly, a major locus (rs13562854 ) on chromosome Dt 3 and a potential candidate gene (CotAD_01947 ) for early maturity were detected. Conclusions This study identified highly favorable SNP alleles and candidate genes associated with early maturity traits in upland cotton. The results demonstrate that GWAS is a powerful tool for dissecting complex traits and identifying candidate genes. The highly favorable SNP alleles and candidate genes for early maturity traits identified in this study should be show high potential for improvement of early maturity in future cotton breeding programs.